2017
DOI: 10.1016/j.tjog.2017.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Maternal serum placental growth factor combined with second trimester aneuploidy screening to predict small-for-gestation neonates without preeclampsia

Abstract: SGA neonates in the absence of PE could potentially be identified at 15-18 weeks of pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Previous studies have reported that the increase of inhibin A is associated with the occurrence of preeclampsia, and fetal malformation and fetal growth restriction [2,[6][7][8][9][10], but there are few reports on inhibin A and other maternal and fetal adverse pregnancy outcomes. The purpose of our study was to evaluate the relationship between inhibition of A and preeclampsia, gestational hypertension, gestational diabetes, macrosomia, low birth weight and preterm delivery in Chinese pregnant women.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that the increase of inhibin A is associated with the occurrence of preeclampsia, and fetal malformation and fetal growth restriction [2,[6][7][8][9][10], but there are few reports on inhibin A and other maternal and fetal adverse pregnancy outcomes. The purpose of our study was to evaluate the relationship between inhibition of A and preeclampsia, gestational hypertension, gestational diabetes, macrosomia, low birth weight and preterm delivery in Chinese pregnant women.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Miranda et al [ 52 ] showed that although mean inhibin A concentrations were significantly higher in women with SGA infants, a multivariable integrative model of maternal characteristics, fetoplacental ultrasound, and maternal biochemical markers only modestly improved the detection of SGA/FGR cases at 32–36 weeks’ gestation when compared with screening based on EFW centiles alone. Other studies [ 53 ] have also shown that the clinical utility of activin A, inhibin A, and follistatin as predictors for SGA/FGR is poor.…”
Section: Hormonal Factors Polypeptides and Glycoproteinsmentioning
confidence: 99%
“…To date, prenatal biochemical screening has largely focused on fetal screening and, to a lesser extent, placenta-related obstetrical outcomes. 32,33 Millions of women worldwide will continue to undergo prenatal biochemical screening; therefore, there exists an opportunity to better estimate a woman's long-term risk of SMM. This study was not designed to test whether prenatal biochemical screening offers additive information over known risk factors for SMM, such as maternal age, high or low body mass index, 23,34 or other risk factors.…”
Section: Clinical and Policy Relevancementioning
confidence: 99%